Induction of specific clonal anergy in human T lymphocytes by Staphylococcus aureus enterotoxins. - O'Hehir, R E (1990)
The exotoxins produced by certain strains of Staphylococcus aureus are able to stimulate powerful polyclonal proliferative responses and to induce nonresponsiveness by clonal deletion of T lymphocytes expressing the appropriate T-cell antigen receptor V beta gene products. This paper examines the ability of S. aureus enterotoxins to modulate the responsiveness of human CD4+ T lymphocytes with defined antigen specificity. It was observed that certain S. aureus toxins were able to activate and induce anergy in hemagglutinin-reactive T cells expressing V beta 3+ elements. After exposure to S. aureus enterotoxins A, B, and D in the absence of antigen-presenting cells, the T cells failed to respond to their natural ligand presented in an immunogenic form, despite enhanced proliferation to exogenous interleukin 2. The S. aureus toxin-induced anergy was associated with modulation of T-cell membrane receptors; down-regulation of the T-cell antigen receptor was concomitant with enhanced expression of CD2 and CD25. Interestingly, CD28 was increased only on stimulation, suggesting this protein may be differentially expressed by activated and anergic T cells. These results indicate that bacterial toxins are able to induce antigen-specific nonresponsiveness in human T cells, the application of which may be relevant in the regulation of T cells expressing a particular family of V beta gene products.